Varijacije, odjeci i tragovi matoševskog flanerizma u izboru iz suvremene hrvatske proze - Gajin, Igor (Wydawnictwo Nauka i Innowacje, 2014)
In his book, Čitanje grada(Reading the City), Krešimir Nemec stated that A.G. Matoš has „modeled after Baudelaire, introduced to the Croatian literature a figure of an idle observer, a curious pedestrian or a flâneur, a typical impressionist product of urban culture and aesthetics of the street”. As a reference and a starting point for reflection on flâneurism’s motifs in contemporary Croatian literature, A.G. Matoš is used as a factor of distinction in outlining one of the most characteristic aspects of the so-called transitional literature. Having said that, a common conclusion is that flâneurismhas, in the Croatian contemporary prose, moved from the streets to the shopping malls. However, contemporary Croatian prose offers the reading of other flâneurism practices as a movement that reflects the changes in categories of urban life, space, daily life and discourse in the transition period from the 20 th to the 21 st century due to the transformative processes such as a transition, globalization and media revolution. Ultimately, Nemec writes: „If he had experienced the present era of electronics and virtual reality, Matoš probably would have called the tireless surfers of the endless Internet sphere electronic flâneurs”.
Variations, Reverbaration and Traces of Matoš’s flâneurism in the Selection of Contemporary Croatian Prose
Keywords: flâneurism; transition; postmodernism; mediasphere; strategies; trajectories